Numerical simulation for cyclic steam injection at Santa Clara field - Rodríguez, Edwin; Barrios, Wilson; Sandoval, Roy; Santos, Nicolás; Cortes, Ingrid (CT&F - Ciencia, Tecnología y Futuro, 2008)
This article presents the methodology used and the results obtained in the construction, match and prediction of the first thermal composition simulation model done in Colombia by employing advanced thermal process commercial software, globally recognized because of its effectiveness in modeling these types of processes (CMG-STARS, 2005). The Santa Clara and Palermo fields were modeled and an excellent history match was achieved. All in all 28 wells and 17 years of production were matched. Two production scenes were proposed. The first involved primary production from existing wells, in other words: primary production; and a second escen where all the wells in the field are converted into injectors and producers, to simulate cyclic steam injection. This injection process included a series of sensitivity studies for several of the parameters involved in this technology, such as: pressure and temperature injection, time and rate of injection, heat injected, soaking period, steam quality, and injection cycles. This sensitivity study was focused on optimizing the processes to obtain the maximum end recovery possible. The information entered into the simulator was validated by laboratory tests developed at the Instituto Colombiano del Petróleo (ICP). Among the tests performed the following were assessed: rock compressibility, relative permeability curve behavior at different temperatures, formation sensitivity to injection fluids, DRX analysis and residual saturation of crude oil for steam injection. The aforementioned results are documented in this paper.